Comprehensive study of key operating parameters on combustion characteristics of butanol-gasoline blends in a high speed SI engine. (15th February 2018) - Liu, Kaimin; Li, Yangtao; Yang, Jing; Deng, Banglin; Feng, Renhua; Huang, Yanjun
Highlights: Common regularities about effects of key variables on combustion were evaluated. Butanol can achieve better knock resistance for allowing earlier ignition timing. The influence of engine load on combustion is greater than that of engine speed. With engine load rising, the net indicated efficiency shows a upward trend. Burning rate of blended fuel is more sensitive to EGR rate than that of gasoline. Abstract: An experimental research were performed in a spark ignition (SI), high speed engine with n -butanol blended ratio of 0%, 30% and 35% by volume to gasoline, and numerical calculation was conducted under different exhaust gas recirculation (EGR) rate and compression ratio combined with knock index (KI) by using GT-Power simulation software. This study aims to find out the common regularities about the effects of key variables such as butanol blend ratio, ignition timing, engine load, EGR rate and compression ratio combined with KI on combustion performance of butanol-gasoline blends in a high speed engine. Results show that, the butanol can achieve better knock resistance in SI engines, which allows earlier ignition timing. After the ignition timing optimized, the peak cylinder pressure (PCP) and the peaks of the rate of heat release (ROHR) rise obviously as the butanol blend ratio increases. Correspondingly, both the locations for PCP and the peaks of ROHR are advanced, which is beneficial to improve thermal power conversion efficiency. The PCP and the rate of pressure rise are obviously influenced by 50% mass fraction burned (MFB) and 10–90% MFB, but the gross indicated thermal efficiency (ITE) and net ITE are not consistent with the changing trend of 50% MFB and 10–90% MFB. The influence of engine load on combustion heat release is greater than that of engine speed. When the engine load increases, the gross ITE increases slightly, but the net ITE shows a noticeable upward trend. The burning rate of butanol-gasoline blends is more sensitive to the change of EGR rate than that of PG, and it is mainly affected by the oxygen concentration and in-cylinder temperature. The increase of compression ratio can boost the in-cylinder maximum combustion temperature, which benefits the improvement of in-cylinder temperature gradient and net ITE, but the rate of net ITE rise gradually decreases with the compression ratio increasing.